Causal Treatment of Acute Cystitis in Pregnant Women - N. V. Sturov; S. V. Popov; O. A. Lesnaya (Антибиотики и Химиотерапия)
Acute cystitis is observed in 1-4% of pregnant women and is potentially dangerous for their health, pregnancy outcomes, and fetal condition. Women with a history of urinary tract infections are especially predisposed to acute cystitis during pregnancy. The article presents approaches to antimicrobial therapy in this category of patients taking into account modern data on resistance of bacteria to various antibiotics. The article emphasizes the expediency of screening, as well as timely diagnosis and treatment of asymptomatic bacteriuria based on data on regional and local antibiotic resistance of uropathogens to improve the results of therapy of acute cystitis in pregnant women.